Indicative Financial Cost of Expanding Shock-Responsive Safety Nets in Senegal - World Bank (World Bank, Washington, DC, 2020)
This policy note is part of a set of documents supporting the development of a national adaptive social protection system in Senegal. The World Bank is supporting the Government of Senegal and specifically the delegation generale a la protection sociale et a la solidarite nationale (DGPSN) through a multidonor trust fund to develop a national adaptive social protection system. A national social protection system integrating tools such as social safety nets reactive to shocks is likely to provide more cost-effective and faster responses to shocks. This note provides a starting point for the establishment of an appropriate funding mechanism by estimating the cost of a food insecurity response in Senegal.